Lithium ion battery

By adding cyclic sulfate and boron-containing additives to the lithium-ion battery to form B-O bonds and CEI films, the performance reduction caused by the dissolution of nickel elements is solved, and the efficient circulation and storage performance of the battery are improved.

CN119208736AInactive Publication Date: 2024-12-27HIGHPOWER TECH HUIZHOU
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202411700766.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The dissolution of nickel elements in existing lithium-ion batteries leads to a reduction in high-temperature cycling and high-temperature storage performance. How to take into account the safety and capacity of the battery is an urgent problem.

Method used

By adding cyclic sulfate additives and boron-containing additives to the electrolyte, the relative relationship between their specific surface area and nickel element content in the positive electrode active material is controlled, and a strong B-O bond is formed to inhibit the dissolution of nickel element, and The CEI film with low impedance and good stability is formed at the positive electrode interface, improving the low-temperature circulation and high-temperature storage performance of the battery.

Benefits of technology

It effectively improves the battery's high voltage and high temperature cycling performance, takes into account the low temperature cycling performance and high temperature storage performance, and improves the battery capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a lithium ion battery, which comprises a positive electrode, a negative electrode and an electrolyte, the positive electrode comprises a positive electrode active material layer, the positive electrode active material layer comprises a positive electrode active material, the positive electrode active material comprises a nickel element-containing compound, and the electrolyte comprises an additive, the additive comprises a cyclic sulfate additive and a boron-containing additive, and the battery meets the relational expression 1: 0.02 < = 100 (X + Y) / (W * A) < = 40; wherein X% is the mass percentage content of the cyclic sulfate additive in the electrolyte; y% is the mass percentage content of the boron-containing additive in the electrolyte; wm < 2 > / g is the surface area of the positive active material; a% is the mass percentage content of the nickel element in the positive electrode active material. According to the battery provided by the invention, the low-temperature cycle performance and the high-temperature cycle performance of the battery can be considered while the battery has relatively high capacity, and meanwhile, the high-temperature storage performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a lithium ion battery. Background Art

[0002] Lithium-ion battery is a high energy density, high efficiency, environmentally friendly battery. Due to its many advantages, it has become the preferred power source for modern electronic devices and small power systems. The basic components of lithium-ion batteries include positive electrode, negative electrode, electrolyte and separator. The negative electrode is the carrier of lithium ions and electrons during the charging process of the battery, and plays the role of energy storage and release.

[0003] The positive electrode material of lithium batteries not only affects battery performance, but is also an important factor in determining battery safety. The positive electrode materials used in existing lithium-ion batteries include lithium cobalt oxide, ternary materials, lithium iron phosphate, etc. Ternary materials contain nickel, cobalt, manganese, and lithium. Under the premise of high safety, lithium nickel cobalt manganese oxide, which mixes three transition metals of nickel, cobalt, and manganese in different proportions, is a positive electrode material with higher safety. During the charging and discharging process of lithium-ion batteries, Ni in the positive electrode material will dissolve and dissolve into the electrolyte. The high-priced Ni element also has high catalytic activity and oxidizability, causing the electrolyte to decompose and generate more by-products, deteriorating the high-temperature cycle performance and high-temperature storage performance of the battery; at the same time, Ni will also be deposited on the negative electrode side to participate in reduction, and the SEI film will dissolve and reconstruct, which will cause the SEI film to decompose, and the Ni element deposited on the negative electrode side will even be reduced to nickel element, causing the negative electrode metal elements to exceed the standard and deteriorate the battery performance.

[0004] Therefore, how to achieve both safety and capacity of high-nickel lithium-ion batteries is an urgent problem to be solved. Summary of the invention

[0005] In order to solve the problem that the nickel content of existing lithium-ion batteries is too high and the Ni element in the positive electrode material is dissolved, causing the high-temperature cycle performance and high-temperature storage performance of the battery to decrease, the present application provides a lithium-ion battery.

[0006] On the one hand, the present application provides a lithium ion battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises a positive electrode active material layer, the positive electrode active material layer comprises a positive electrode active material, the positive electrode active material comprises a compound containing a nickel element, the electrolyte comprises an additive, the additive comprises a cyclic sulfate additive and a boron-containing additive, The battery satisfies the relationship 1: 0.02≤100(X+Y) / (W×A)≤40 Formula 1 Wherein, X% is the mass percentage of the cyclic sulfate additive in the electrolyte; Y% is the mass percentage of the boron-containing additive in the electrolyte; Wm2 / g is the surface area of ​​the positive electrode active material; A% is the mass percentage of the nickel element in the positive electrode active material.

[0007] Preferably, the battery satisfies Relationship 2: 1.7≤100(X+Y) / (W×A)≤16.7 Equation 2.

[0008] Preferably, X=0.5~4.

[0009] Preferably, Y=0.1~2.

[0010] Preferably, the battery further satisfies the relationship formula 3: XY≥-1 Formula 3; and 0.5≤X≤4, 0.1≤Y≤2.

[0011] Preferably, 0.3≤W≤1.5.

[0012] Preferably, 30≤A≤90.

[0013] Preferably, the cyclic sulfate additive comprises at least one of the following compounds: .

[0014] Preferably, the boron-containing additives include boron trifluoride-pyridine, boron trifluoride-triphenylphosphine oxide, boron trifluoride-trimethyl phosphate, boron trifluoride-pyrazine, boron trifluoride-triazine, tris(pentafluorophenyl)borane, lithium bis(oxalato)borate, lithium difluorooxalato)borate, lithium tetrafluoroborate, lithium tetracyanoborate, lithium tetra(trifluoromethyl)borate, lithium (trifluoromethyl) trifluoroborate, lithium bis(trifluoromethyl) difluoroborate, lithium pentafluoroethyl trifluoroborate, lithium dicyanooxalato)borate, lithium bis(malonate)borate, One or more of lithium (2-fluoromalonate) difluoroborate, lithium tetramethoxyborate, lithium tetraethoxyborate, lithium sulfate (trifluoroborate), lithium difluoroborate, methanedisulfonate lithium difluoroborate, trimethyl borate, triethyl borate, tripropyl borate, tributyl borate, tri(2,2,2-trifluoroethyl) borate, tri(trimethylsilyl) borate, tri(triethylsilyl) borate, tri(pentafluorophenyl) borate, tripropargyl borate, and tri(2-cyanoethyl) borate.

[0015] Preferably, the positive electrode further comprises a positive electrode current collector, and the positive electrode active material layer is coated on at least one side surface of the positive electrode current collector; The chemical formula of the positive electrode active material is LiNi a Cob Mn (1-a-b) M c O2, wherein 0.3≤a≤0.9, a+b<1, 0≤c<0.08, and M is one or more of Al, Mg, Zr and Ti; The negative electrode comprises a negative electrode current collector and a negative electrode active material layer coated on at least one side of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2 or spinel structured lithiated TiO2-Li4Ti5O 12 , Li-Al alloy or more.

[0016] The battery provided by the present application satisfies the relationship of 0.02≤100(X+Y) / (W×A)≤40 by controlling the relative relationship between the content of cyclic sulfate ester additives and boron-containing additives in the electrolyte and the specific surface area of ​​the positive electrode active material and the content of Ni element in the positive electrode active material. The cyclic sulfate ester additives and the boron-containing additives work together, and the boron-containing additives form a strong B-O bond with the oxygen on the surface of the positive electrode, thereby passivating the electrode to inhibit the side reaction caused by the release of oxygen by the positive electrode active material. At the same time, the B-O bond can effectively complex Ni atoms and inhibit the dissolution of Ni, thereby improving the high-voltage and high-temperature cycle performance of the battery; the cyclic sulfate ester additive is oxidized at the positive electrode interface to form a low-impedance and stable CEI film, which can effectively improve the low-temperature cycle performance and high-temperature storage gas production of the battery, and is reduced at the negative electrode to generate a stable SEI film, thereby improving the high-temperature cycle performance and high-temperature storage performance of the battery. The battery provided by the present application can take into account the low-temperature cycle performance and high-temperature cycle performance of the battery while having a high capacity, and at the same time improve the high-temperature storage performance of the battery. DETAILED DESCRIPTION

[0017] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0018] In order to illustrate the technical solution of the present invention, specific embodiments are provided below for illustration.

[0019] On the one hand, an embodiment of the present application provides a lithium ion battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises a positive electrode active material layer, the positive electrode active material layer comprises a positive electrode active material, the positive electrode active material comprises a compound containing a nickel element, the electrolyte comprises an additive, the additive comprises a cyclic sulfate additive and a boron-containing additive, The battery satisfies the relationship 1: 0.02≤100(X+Y) / (W×A)≤40 Formula 1 Wherein, X% is the mass percentage of the cyclic sulfate additive in the electrolyte; Y% is the mass percentage of the boron-containing additive in the electrolyte; Wm 2 / g is the surface area of ​​the positive electrode active material; A% is the mass percentage of the nickel element in the positive electrode active material.

[0020] The inventors have found that the performance of the battery is significantly correlated with the specific surface area of ​​the positive electrode active material and the Ni content in the positive electrode active material. Increasing the Ni content in the positive electrode active material will increase the capacity of the battery, but an increase in the nickel content will increase the probability of nickel dissolution, and deteriorate the high-temperature cycle and high-temperature storage performance of the battery; increasing the specific area of ​​the positive electrode active material layer will increase the chance of contact between the electrolyte and the electrode interface, and the low-temperature fast charging performance will be better, but this will be accompanied by an increase in side reactions, and worse high-temperature storage and high-temperature cycling.

[0021] Boron-containing additives are added to the electrolyte of lithium-ion batteries. The film formation mechanism of boron-containing additives at the positive electrode is that the boron-containing additives are oxidized to separate from CO2 and form stable acyl radicals. The acyl radicals are reorganized at the positive electrode oxide-electrolyte interface and generate borane dimers. The borane dimers form strong B-O bonds with the oxygen on the positive electrode surface, thereby passivating the electrode and inhibiting the side reactions caused by the release of oxygen by the positive electrode active material; at the same time, the B-O bond can effectively complex Ni atoms, inhibit Ni dissolution, reduce Ni dissolution probability and dissolution content, thereby improving the high-voltage and high-temperature cycle performance of the battery. However, the impedance of boron-containing additives is relatively large, which deteriorates the low-temperature cycle performance to a certain extent. At the same time, boron-containing additives are easy to decompose at high temperatures, which will deteriorate high-temperature storage to a certain extent.

[0022] Cyclic sulfate additives have a higher HOMO energy level, and preferentially oxidize at the positive electrode interface to form a CEI film rich in RSO3Li with high ion conductivity and stability, which significantly improves the gas production and safety performance of the battery in low-temperature cycling and high-temperature storage; in addition, cyclic sulfate additives also have a lower LUMO energy level, and preferentially reduce at the negative electrode to form a high-quality SEI film before the solvent in the electrolyte, which improves the high-temperature cycling performance and high-temperature storage performance of the battery. Therefore, in order to solve the above problems, cyclic sulfate additives and boron-containing additives are added to the electrolyte of lithium-ion batteries at the same time. Due to the low impedance interface formed by the cyclic sulfate additives at the positive electrode interface, the low-temperature cycling performance of the battery can be effectively improved. At the same time, the CEI interface film formed by the cyclic sulfate additives has better thermal stability, which can significantly improve the high-temperature storage performance. When the cyclic sulfate additives and the boron-containing additives are used together, the battery satisfies the relationship 0.02≤100(X+Y) / (W×A)≤40, which can effectively take into account the low-temperature cycling performance and high-temperature cycling performance of the battery, and improve the high-temperature storage performance.

[0023] The battery provided by the present application satisfies the relationship of 0.02≤100(X+Y) / (W×A)≤40 by controlling the relative relationship between the content of cyclic sulfate ester additives and boron-containing additives in the electrolyte and the specific surface area of ​​the positive electrode active material and the content of Ni element in the positive electrode active material. The cyclic sulfate ester additives and the boron-containing additives work together, and the boron-containing additives form a strong B-O bond with the oxygen on the surface of the positive electrode, thereby passivating the electrode to inhibit the side reaction caused by the release of oxygen by the positive electrode active material. At the same time, the B-O bond can effectively complex Ni atoms and inhibit the dissolution of Ni, thereby improving the high-voltage and high-temperature cycle performance of the battery; the cyclic sulfate ester additive is oxidized at the positive electrode interface to form a low-impedance and stable CEI film, which can effectively improve the low-temperature cycle performance and high-temperature storage gas production of the battery, and is reduced at the negative electrode to generate a stable SEI film, thereby improving the high-temperature cycle performance and high-temperature storage performance of the battery. The battery provided by the present application can take into account the low-temperature cycle performance and high-temperature cycle performance of the battery while having a high capacity, and at the same time improve the high-temperature storage performance of the battery.

[0024] If the battery does not satisfy the relationship 0.02≤100(X+Y) / (W×A)≤40, if 100(X+Y) / (W×A) is less than 0.02, the content of cyclic sulfate additives and boron-containing additives is too low relative to the specific surface area of ​​the positive electrode active material and the Ni content in the positive electrode active material, and the effect of effectively improving the high-temperature cycle and high-temperature storage performance of the battery cannot be achieved; if 100(X+Y) / (W×A) is greater than 40, the boron-containing additives are too much, and the high-temperature storage performance and low-temperature cycle performance of the battery are poor; or the Ni content is too low, and the capacity of the battery is low.

[0025] In some preferred embodiments, the battery satisfies Relationship 2: 1.7≤100(X+Y) / (W×A)≤16.7 Equation 2.

[0026] The content of cyclic sulfate additives and boron-containing additives in the battery, the specific surface area of ​​the positive electrode active material, and the content of Ni in the positive electrode active material satisfy the relationship 1.7≤100(X+Y) / (W×A)≤16.7. The battery has better low-temperature cycle performance and high-temperature cycle performance and higher capacity. At the same time, the battery produces less gas and has higher high-temperature storage performance.

[0027] In some embodiments, X=0.5~4.

[0028] Specifically, the mass percentage of the cyclic sulfate ester additive in the electrolyte is X%, where X is 0.5-4.

[0029] When X is in the range of 0.5 to 4, it is helpful for the cyclic sulfate additive to oxidize at the positive electrode interface to form a low-impedance, stable CEI film, which can effectively improve the low-temperature cycle performance and high-temperature storage gas production of the battery, and reduce at the negative electrode to form a stable SEI film, improving the high-temperature cycle performance and high-temperature storage performance of the battery. When the mass percentage of the cyclic sulfate additive in the electrolyte is too low, it cannot achieve a good effect; when the mass percentage of the cyclic sulfate additive in the electrolyte is too high, the cycle performance will be deteriorated. At this time, due to the excessively high content of the additive, the viscosity of the electrolyte will increase, resulting in poor battery rate performance.

[0030] Specifically, the value of X can be 0.5, 1.0, 1.5, 2.0, 2.5, 2.8, 3.2, 3.5, 4.0, etc., as long as X is in the range of 0.5 to 4.

[0031] In some embodiments, Y=0.1~2.

[0032] Specifically, the mass percentage of the boron-containing additive in the electrolyte is Y%, and Y is 0.1-2. When Y is in the range of 0.1-2, it is helpful for the boron-containing additive to be oxidized, detach from CO2 and form stable acyl radicals. The acyl radicals reorganize at the positive electrode oxide-electrolyte interface and generate borane dimers. The borane dimers form strong B-O bonds with the oxygen on the positive electrode surface, thereby passivating the electrode and inhibiting the side reactions caused by the release of oxygen by the positive electrode active material; at the same time, the B-O bond can effectively complex Ni atoms and inhibit the dissolution of Ni, thereby improving the high-voltage and high-temperature cycle performance of the battery. When the mass percentage of the boron-containing additive in the electrolyte is too low, it cannot achieve a good effect; when the mass percentage of the boron-containing additive in the electrolyte is too high, it will deteriorate the storage performance and low-temperature fast charging performance.

[0033] Specifically, the value of Y can be 0.1, 0.3, 0.5, 0.7, 1.0, 1.2, 1.3, 1.5, 1.7, 2.0, etc., as long as Y is in the range of 0.1~2.

[0034] In some embodiments, 0.3≤W≤1.5 Specifically, the surface area of ​​the positive electrode active material is W m 2 / g, 0.3≤W≤1.5. When W is in the range of 0.3≤W≤1.5, the specific area of ​​the positive electrode active material layer is increased, the opportunity for contact between the electrolyte and the positive electrode interface is increased, the low-temperature fast charging performance of the battery is improved, and the low-temperature cycle performance of the battery is improved. However, if the specific area of ​​the positive electrode active material layer is too large, the side reactions at the interface between the electrolyte and the electrode will increase, and the cycle performance and high-temperature storage performance of the battery will deteriorate. When the specific surface area W of the positive electrode active material is limited to the range of 0.3≤W≤1.5 in the embodiment of the present application, the rate performance and safety performance of the battery can be better balanced.

[0035] Specifically, the value of W can be 0.3, 0.5, 0.7, 1.0, 1.2, 1.3, 1.5, etc., as long as Y is in the range of 0.3~1.5.

[0036] In some embodiments, 30≤A≤90.

[0037] Specifically, the mass percentage of the nickel element in the positive electrode active material is A%, 30≤A≤90.

[0038] When A is in the range of 30~90, increasing the nickel element in the positive electrode active material can increase the capacity of the battery. The resulting battery can take into account the low-temperature cycle performance and high-temperature cycle performance of the battery, while improving the high-temperature storage performance of the battery, and also has a higher capacity. However, if the Ni content is too high, the cycle performance and thermal shock performance will deteriorate sharply, and if the content is too low, the effect of increasing the battery capacity cannot be achieved. Therefore, when the content A of the Ni element in the positive electrode active material is limited to 30≤A≤90 in the embodiment of the present application, the energy density and performance of the battery can be better balanced.

[0039] Specifically, the value of A can be 30, 33, 35, 40, 50, 60, 70, 80, 90, etc., as long as A is within the range of 30~90.

[0040] In some implementations, the battery further satisfies Relationship Formula 3: XY≥-1 Formula 3; and 0.5≤X≤4, 0.1≤Y≤2.

[0041] Specifically, excessive boron-containing additives will deteriorate high-temperature storage performance, and large impedance will deteriorate low-temperature cycling performance; while cyclic sulfate ester additives can form films with good thermal stability at both the positive and negative electrodes, which can improve high-temperature storage performance and high-temperature cycling performance. At the same time, the CEI interface film formed by cyclic sulfate ester additives has low impedance, which can improve the low-temperature cycling performance of the battery.

[0042] When the amount Y of the boron-containing additive added to the electrolyte and the amount X of the cyclic sulfate additive added satisfy equation 3: XY≥-1 equation 3, and satisfy 0.5≤X≤4, 0.1≤Y≤2, the synergistic effect of the two can be effectively exerted to significantly improve the low-temperature cycle performance, high-temperature cycle performance and high-temperature storage performance of the battery.

[0043] In some embodiments, the cyclic sulfate ester additive includes at least one of the following compounds: .

[0044] In some embodiments, the boron-containing additive includes boron trifluoride-pyridine, boron trifluoride-triphenylphosphine oxide, boron trifluoride-trimethyl phosphate, boron trifluoride-pyrazine, boron trifluoride-triazine, tris(pentafluorophenyl)borane, lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium tetrafluoroborate (LIBF4), lithium tetracyanoborate, lithium tetra(trifluoromethyl)borate, lithium (trifluoromethyl) trifluoroborate, lithium bis(trifluoromethyl) difluoroborate, lithium pentafluoroethyl trifluoroborate, lithium dicyanoborate, bis(trifluoromethyl) trifluoroborate, lithium di(oxalatoborate), lithium di(propanediol) One or more of lithium borate, (2-fluoromalonate) lithium difluoroborate, lithium tetramethoxyborate, lithium tetraethoxyborate, dilithium sulfate (trifluoroborate), lithium difluoroborate, methanedisulfonate lithium difluoroborate, trimethyl borate (TMB), triethyl borate, tripropyl borate, tributyl borate, tri(2,2,2-trifluoroethyl) borate, tris(trimethylsilyl)borate (TMSB), tris(triethylsilyl) borate, tris(pentafluorophenyl) borate, tripropargyl borate, and tris(2-cyanoethyl)borate.

[0045] In some embodiments, the electrolyte also includes an electrolyte salt, and the electrolyte salt includes one or more of lithium hexafluorophosphate LiPF6, lithium difluorooxalatoborate LiODFB, lithium bis(oxalatoborate) LiBOB, lithium difluorobis(oxalatophosphate) LiDFOP, lithium tetrafluoroborate LiBF4, lithium bis(trifluoromethylsulfonyl)imide LiTFSI, lithium bis(fluorosulfonyl)imide LiFSI, and lithium difluorophosphate LiPOF2. In the electrolyte, the concentration of the electrolyte salt is 0.4 mol / L~2.2 mol / L.

[0046] In some embodiments, the electrolyte also includes an organic solvent, and the organic solvent includes at least one of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methyl propyl carbonate, diphenyl carbonate, methyl acetate, methyl propionate, methyl butyrate, methyl acetate, ethyl acetate, propyl acetate, ethyl butyrate, propyl propionate, γ-butyrolactone, 1,3-dioxolane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.

[0047] In some embodiments, the positive electrode further comprises a positive electrode current collector, and the positive electrode active material layer is coated on at least one side of the positive electrode current collector; The chemical formula of the positive electrode active material is LiNi a Co b Mn (1-a-b) M c O2, wherein 0.3≤a≤0.9, a+b<1, 0≤c<0.08, and M is one or more of Al, Mg, Zr and Ti; In the embodiments of the present application, there is no particular restriction on the type of the positive electrode current collector, which can be any known material suitable for use as a positive electrode current collector. In one embodiment, the positive electrode current collector includes metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and carbon materials such as carbon cloth and carbon paper. Preferably, the positive electrode current collector is a metal material.

[0048] In some embodiments, the positive electrode active material layer further includes a positive electrode conductor, a positive electrode binder and an organic solvent.

[0049] In some embodiments, the positive electrode conductive agent includes at least one of carbon materials such as natural graphite, artificial graphite, acetylene black, needle coke, carbon nanotubes, and graphene.

[0050] In some embodiments, the positive electrode binder includes at least one of polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, and nitrocellulose.

[0051] In some embodiments, the lithium-ion battery further comprises a separator, which is disposed between the positive electrode sheet and the negative electrode sheet. There is no particular limitation on the material and shape of the separator, as long as the effect of the present application is not significantly impaired.

[0052] The diaphragm includes a porous sheet or non-woven fabric with excellent liquid retention, etc. For example, the diaphragm can be a resin or glass fiber diaphragm material. The diaphragm includes but is not limited to polyolefins, aromatic polyamides, polytetrafluoroethylene, polyether sulfone, etc.

[0053] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet are assembled to form an electrode assembly, and the battery may include an outer packaging, which can be used to encapsulate the above-mentioned electrode assembly and the electrolyte.

[0054] In some embodiments, the outer packaging of the lithium-ion battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc.; the outer packaging can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0055] The present application has no particular limitation on the shape of the lithium-ion battery, which may be cylindrical, square, or any other shape.

[0056] In the embodiment of the present application, the negative electrode includes a negative electrode current collector and a negative electrode active material layer, the negative electrode active material layer is coated on at least one side of the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, a negative electrode binder and a negative electrode conductive agent, and the negative electrode active material includes natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 , Li-Al alloy.

[0057] The embodiments of the present application have no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, it can be copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite current collector.

[0058] In some embodiments, the negative electrode conductive agent includes at least one of carbon materials such as natural graphite, artificial graphite, acetylene black, needle coke, carbon nanotubes, and graphene.

[0059] In some embodiments, the negative electrode binder includes at least one of polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, and nitrocellulose.

[0060] The present application also provides an electrical device, including the above-mentioned lithium-ion battery.

[0061] Exemplarily, the above-mentioned electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0062] The present invention is further described below by way of examples.

[0063] Example 1

[0064] Preparation of positive electrode The positive electrode active material, positive electrode conductive agent acetylene black (SuperP) and polyvinylidene fluoride (PVDF) binder are mixed evenly in a mass ratio of 97:1.5:1.5, and evenly dispersed with 1-methyl-2-pyrrolidone (NMP) to form a uniform positive electrode slurry. The mixed slurry is coated on both sides of the aluminum foil current collector, and then baked, rolled and cut into pieces to obtain the positive electrode sheet. The chemical formula of the positive electrode active material used is LiNi 0.8 Co 0.1 Mn 0.1 O2.

[0065] Among them, the specific surface area of ​​the positive electrode active material Wm 2 / g and the content of Ni element in the positive electrode active material A%, and the specific values ​​of W and A are shown in Table 1.

[0066] The content of Ni element in the positive electrode active material can be detected by the following method: The positive electrode active material layer on the positive electrode sheet was scraped off, and 5 mg of the positive electrode active material layer was added with 3 mL of concentrated sulfuric acid and 3 mL of concentrated nitric acid in sequence, and heated to 180°C until the solution was clear and transparent. After cooling, water was added to make the volume 50 mL, and the sample was sent for detection. The content of the metal Ni element therein was tested using an ICP (Inductive Coupled Plasma Emission Spectrometer).

[0067] Preparation of negative electrode The negative electrode active material graphite, the negative electrode conductive agent acetylene black (Super P), the thickener CMC and the negative electrode binder SBR are mixed evenly in a mass ratio of 94:2:1.2:2.8, and evenly dispersed with deionized water to form a uniform negative electrode slurry. The mixed slurry is coated on both sides of the copper foil current collector, and then baked, rolled and cut into pieces to obtain the negative electrode sheet.

[0068] Preparation of electrolyte a. Ethylene carbonate (EC), propylene carbonate (PC), propyl propionate (EP) and diethyl carbonate (DEC) were mixed and stirred in a mass ratio of 10:20:40:30 to form a mixed solvent, and water was removed by molecular sieves for later use. 1M LiPF6 was added and mixed evenly; b. Add additives and lithium hexafluorophosphate to the colorless transparent liquid obtained in step a to obtain an electrolyte, wherein the molar concentration of lithium hexafluorophosphate is 1.0 mol / L. The additives include cyclic vinyl sulfate and boron-containing additives, the mass percentage of the cyclic sulfate additive in the electrolyte is X%, and the mass percentage of the boron-containing additive in the electrolyte is Y%, wherein the specific values ​​of X and Y are shown in Table 1.

[0069] Lithium-ion battery manufacturing The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator placed between the positive and negative electrode sheets, and the bare battery cell is obtained by winding and welding the tabs. The bare battery cell is placed in an aluminum-plastic film, liquid is injected, and packaged to obtain a lithium-ion battery.

[0070] Examples 2 to 57 and Comparative Examples 1 to 9 Most of the steps of Examples 2 to 57 and Comparative Examples 1 to 9 are the same as those of Example 1, except that the types and contents of the cyclic vinyl sulfate and the boron-containing additive in the electrolyte are different, as shown in Table 1, Table 2 and Table 3; The specific surface area Wm of the positive electrode active material 2 / g, the content A% of nickel in the positive electrode active material is different, and the specific values ​​are shown in Table 1, Table 2 and Table 3. Among them, Table 1 is Examples 1-20, Table 2 is Examples 21-40, Table 3 is Examples 41-57, and Comparative Examples 1-9.

[0071] Table 1

[0072] Table 2

[0073] Table 3

[0074] Performance Testing The lithium-ion batteries prepared in the above-mentioned embodiments and comparative examples were subjected to the following tests.

[0075] 60℃ storage performance test In a 25±2℃ constant temperature box, charge the lithium-ion battery to 4.40V at 1C constant current and constant voltage, with a cut-off current of 0.05C, and test the thickness of the lithium-ion battery (this is the thickness before storage). Place the fully charged cell / battery at (60±2)℃ for 35 days in an open circuit, and after 35 days of storage, place it in an open circuit at room temperature for 2 hours, test the thickness after storage, and calculate the thickness expansion rate of the lithium-ion battery: Thickness expansion rate = [(thickness after storage - thickness before storage) / thickness before storage] × 100% 45℃ Cyclic Performance Test In a 45±2℃ constant temperature box, the lithium-ion battery was charged to 4.40V at 1C constant current and constant voltage, with a cut-off current of 0.05C, and then discharged to 3V at 1C. Multiple charge and discharge cycles were performed under the above conditions, and the capacity retention rate of the battery after 600 cycles was calculated, with 5 batteries in each group.

[0076] Capacity retention rate (%) = 600th cycle discharge capacity (mAh) / third cycle discharge capacity (mAh) * 100%.

[0077] The average value of the capacity retention rate of each group of 5 batteries after different cycles is recorded in Table 2.

[0078] 0℃ charge capacity retention rate In a 0±2℃ constant temperature box, the lithium-ion battery was charged to 4.40V at 1C constant current and constant voltage, the cut-off current was 0.05C, and then discharged to 3V at 1C. Multiple charge and discharge cycles were performed under the above conditions, and the capacity retention rate of the battery after 600 cycles was calculated, with 5 batteries in each group.

[0079] Capacity retention rate (%) = 600th cycle discharge capacity (mAh) / third cycle discharge capacity (mAh) * 100% The average values ​​of the capacity retention rates of the five batteries in each group after different cycles are recorded in Tables 4, 5 and 6.

[0080] The above test results are shown in Table 4, Table 5 and Table 6.

[0081] Table 4

[0082] Table 5

[0083] Table 6

[0084] According to Tables 1-3 and 4-6, it can be concluded that, by comparing Example 1 with Comparative Examples 1-9, there is no cyclic sulfate additive and boron-containing additive in Comparative Example 1, the battery produces more gas during high-temperature storage, and the low-temperature cycle and high-temperature cycle performances are poor; Comparative Example 2 only adds boron-containing additives, Comparative Example 3 only adds cyclic sulfate additives, Comparative Examples 4-5 add boron-containing additives but no cyclic sulfate additives, Comparative Examples 6-7 add cyclic sulfate additives but no boron-containing additives, and the high-temperature storage of the battery, the high-temperature storage, low-temperature cycle and high-temperature cycle performances of the batteries of Comparative Examples 2-7 are still poor; although cyclic sulfate additives and boron-containing additives are added to Comparative Examples 8-9, the batteries do not satisfy the relationship 0.02≤100(X+Y) / (W×A)≤40, The battery's cycling and high-temperature storage performance are still poor, indicating that by adding cyclic sulfate additives and boron-containing additives to the electrolyte, and at the same time the battery satisfies the relationship 0.02≤100(X+Y) / (W×A)≤40, the cyclic sulfate additives and boron-containing additives work together, and the boron-containing additives form a strong B-O bond with the oxygen on the positive electrode surface, thereby passivating the electrode and inhibiting the side reaction caused by the release of oxygen by the positive electrode active substance. At the same time, the B-O bond can effectively complex Ni atoms and inhibit the dissolution of Ni, thereby improving the high-voltage and high-temperature cycling performance of the battery; the cyclic sulfate additive is oxidized at the positive electrode interface to form a low-impedance, stable CEI film, which can effectively improve the low-temperature cycling performance and high-temperature storage gas production of the battery, and is reduced at the negative electrode to form a stable SEI film, thereby improving the high-temperature cycling performance and high-temperature storage performance of the battery.

[0085] Compared with Examples 1-21 and Examples 41-49 and 51, X is in the range of 0.5~4, Y is in the range of 0.1~2, 0.3≤W≤1.5, 30≤A≤90, and the battery satisfies the relationship 0.02≤100(X+Y) / (W×A)≤40, the high temperature storage thickness expansion rate of the battery is low, the high temperature cycle capacity retention rate is high, and the low temperature cycle capacity retention rate is high; further preferably, the battery satisfies the relationship 1.7≤100(X+Y) / (W×A)≤16.7, the high temperature cycle and low temperature cycle capacity retention rates of the battery are higher, and gas production is less.

[0086] Comparison of Examples 1 and 24-39 shows that changing the types of cyclic sulfate ester additives and boron-containing additives, as long as they meet the range specified in this application, can improve the high-temperature cycle and low-temperature cycle of the battery and improve the high-temperature storage performance of the battery. Comparison of Example 1 and Example 40, the types of cyclic sulfate ester additives meet the requirements of this application, and the battery satisfies the relationship 0.02≤100(X+Y) / (W×A)≤40, the battery has good high-temperature cycle performance and low-temperature cycle performance, low high-temperature storage thickness expansion rate, and less gas production.

[0087] A comparison between Examples 1-21 and Examples 52-57 shows that the battery satisfies the relationship 0.02≤100(X+Y) / (W×A)≤40, and also satisfies the relationship 3: XY≥-1 Formula 3; and when the conditions are 0.5≤X≤4, 0.1≤Y≤2, the high temperature cycle and low temperature cycle capacity retention rates of the battery are high, and the high temperature storage thickness expansion rate of the battery is low, and the gas production is small.

[0088] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, it should be understood by those skilled in the art that the technical solutions described in the above embodiments can still be modified, or some of the technical features can be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention, and should be included in the protection scope of the present invention.

Claims

1. A lithium ion battery, characterized in that: The invention comprises a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises a positive electrode active material layer, the positive electrode active material layer comprises a positive electrode active material, the positive electrode active material comprises a compound containing nickel element, the electrolyte comprises an additive, the additive comprises a cyclic sulfate additive and a boron-containing additive, The battery satisfies the relationship 1: 0.02≤100(X+Y) / (W×A)≤40 Formula 1 Wherein, X% is the mass percentage of the cyclic sulfate additive in the electrolyte; Y% is the mass percentage of the boron-containing additive in the electrolyte; Wm 2 / g is the surface area of ​​the positive electrode active material; A% is the mass percentage of the nickel element in the positive electrode active material.

2. The lithium-ion battery according to claim 1, characterized in that The battery satisfies the relationship 2: 1.7≤100(X+Y) / (W×A)≤16.7 Equation 2.

3. The lithium ion battery according to claim 1 or 2, characterized in that: X=0.5~4。 4. The lithium ion battery according to claim 1 or 2, characterized in that: Y=0.1~2。 5. The lithium-ion battery according to claim 1, characterized in that: The battery also satisfies Relation 3: XY≥-1 Formula 3; and 0.5≤X≤4, 0.1≤Y≤2.

6. The lithium ion battery according to claim 1 or 2, characterized in that: 0.3≤W≤1.5。 7. The lithium ion battery according to claim 1 or 2, characterized in that: 30≤A≤90。 8. The lithium-ion battery according to claim 1, characterized in that The cyclic sulfate additive includes at least one of the following compounds: 。 9. The lithium-ion battery according to claim 1, characterized in that: The boron-containing additives include boron trifluoride-pyridine, boron trifluoride-triphenylphosphine oxide, boron trifluoride-trimethyl phosphate, boron trifluoride-pyrazine, boron trifluoride-triazine, tris(pentafluorophenyl)borane, lithium bis(oxalato)borate, lithium difluorooxalato)borate, lithium tetrafluoroborate, lithium tetracyanoborate, lithium tetra(trifluoromethyl)borate, lithium (trifluoromethyl) trifluoroborate, lithium bis(trifluoromethyl) difluoroborate, lithium pentafluoroethyl trifluoroborate, lithium dicyanooxalato)borate, lithium bis(malonate)borate, (2 The invention can be selected from the group consisting of lithium bis(trifluoroborate), lithium tetramethoxyborate, lithium tetraethoxyborate, lithium sulfate (trifluoroborate), lithium difluoroborate, methanedisulfonate lithium difluoroborate, trimethyl borate, triethyl borate, tripropyl borate, tributyl borate, tri(2,2,2-trifluoroethyl) borate, tris(trimethylsilyl) borate, tris(triethylsilyl) borate, tris(pentafluorophenyl) borate, tripropargyl borate, and tris(2-cyanoethyl) borate.

10. The lithium ion battery according to claim 1, characterized in that: The positive electrode further comprises a positive electrode current collector, and the positive electrode active material layer is coated on at least one side of the surface of the positive electrode current collector; The chemical formula of the positive electrode active material is LiNi a Co b Mn (1-a-b) M c O2, wherein 0.3≤a≤0.9, a+b<1, 0≤c<0.08, and M is one or more of Al, Mg, Zr and Ti; The negative electrode comprises a negative electrode current collector and a negative electrode active material layer coated on at least one side of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2 or spinel structured lithiated TiO2-Li4Ti5O 12 , Li-Al alloy or more.

Citation Information

Patent Citations

  • Quick-charging type lithium-ion battery and preparation method thereof

    CN108428867A

  • Lithium ion battery and preparation method thereof

    CN111628218A

  • Positive electrode active material, positive electrode plate and lithium ion secondary battery

    CN112447965A

  • Lithium ion battery

    CN115020814A

  • Positive electrode slurry, preparation method thereof and lithium ion battery

    CN115050949A